Atividade anti-melanoma da indometacina incorporada em partículas de sílica nanoestruturada - Ferreira, Natália Helen (2021)
Melanoma represents the smallest number of skin cancer cases; however, it is the most lethal type among skin cancers. This is due to factors such as their highly metastatic nature, unexpected evolution and inefficiency of current systemic treatments, mainly due to the high toxicity and resistance acquired to these treatments. In this sense, there is a need to find additional treatments that directly address tumor survival, targeting apoptotic pathways that may increase tumor cell sensitivity to drugs and minimize toxicity, which is often associated with conventional therapies. Indomethacin (IND) is known to promote mitochondrial oxidative stress and the generation of reactive oxygen species, which are known to modulate intrinsic signaling of mitochondria-mediated apoptosis. Despite its wide distribution and therapeutic use, IND has undesirable gastrointestinal effects, such as ulcerations, hemorrhages, inhibiting platelet aggregation, is associated with renal toxicity and central nervous system disorders, and its toxicity is dose dependent. In order to reduce the toxic effects of this drug, the present study investigated the antitumor efficiency of IND incorporated in mesoporous silica nanoparticles (MSNPs+IND), as well as the toxic potential of treatments in syngeneic murine B16 melanoma model. Male C57BL/6 mice were implanted subcutaneously with B16F10 cells. The animals received once daily, for five consecutive days, treatments with IND (2.5 and 5.0 mg/kg body weight [b.w.]) and MSNPs+IND (16.66 and 33.33 mg/kg b.w. [15% of IND incorporated into the MSNPs]). Evaluation of antitumor activity was performed by measuring size, tumor weight and histopathological analysis. Possible molecular signaling pathways involved in antitumor activity were analyzed by Western blot assays in liver tissue and immunohistochemistry in tumor tissue. At the same time, the potential toxicity of the treatments was evaluated by varying body mass and organs, quantifying the biochemical indicators of renal damage (creatinine and urea) and bone marrow genotoxicity. The results of the present study demonstrated that treatments with MSNPs+IND 2.5 and 5.0 showed antitumor activity, leading to 54.18 and 70.09% inhibition of tumor growth, respectively. Histopathological analysis revealed a decrease in the frequency of mitosis in the tumor tissues of the groups treated with MSNPs+IND 2.5 and 5.0, being 37.95 and 35.90% lower, respectively, compared to the IND 2.5 and 5 groups. .0. The observed antitumor activity may be related to the inhibition of COX-2, the main mechanism of action of IND. In hepatic tissue, COX-2 levels decreased significantly after treatment with MSNPs+IND and IND. In this context, it is shown that MSNPs were able to control IND delivery at the tumor site, and gradual release of the drug was responsible for the antitumor activity, inhibiting COX-2 and blocking cell proliferation. Additionally, the observed antitumor activity may also be related to the increased expression of cleaved caspase-3, which increased by 156.25 and 137.50% for the groups treated with MSNPs+IND and IND, respectively, which possibly induced tumor cells to apoptosis. Regarding toxic effects, there were no significant differences in weight gain and animal organ weight between the different treatment groups. Serum creatinine and urea levels did not differ significantly, indicating no nephrotoxicity for the different treatment groups. Finally, in the bone marrow genotoxic analysis, an increase in the frequency of micronuclei was observed for the group treated with IND 5.0, indicating genotoxicity. However, no significant differences were observed for the MSNPs+IND groups, indicating that the MSNPs were efficient in preventing the genotoxic effect of IND in this parameter. Thus, MSNPs nanocarriers may therefore be promising for future applications in cancer therapy. Keywords: Indomethacin; Mesoporous silica nanoparticles; Anti-melanoma activity; COX-2; Apoptosis.